2021
DOI: 10.1155/2021/5548310
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Statin Therapy on Arterial Stiffness

Abstract: Arterial stiffness describes the increased rigidity of the arterial wall that occurs as a consequence of biological aging and several diseases. Numerous studies have demonstrated that parameters to assess arterial stiffness, especially pulse-wave velocity, are predictive of those individuals that will suffer cardiovascular morbidity and mortality. Statin therapy may be a pharmacological strategy to improve arterial elasticity. It has been shown that the positive benefits of statin therapy on cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 132 publications
0
17
0
3
Order By: Relevance
“…However, the long-term effect by ACE or ARBs on pulse wave velocity is not clear. Similarly, studies have suggested, that statin treatment lowers aortic stiffness [ 18 , 19 ]. The exact mechanisms is not clear but reduction of the vascular remodeling and vascular tone in combination with reduced oxidative stress have been suggested [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the long-term effect by ACE or ARBs on pulse wave velocity is not clear. Similarly, studies have suggested, that statin treatment lowers aortic stiffness [ 18 , 19 ]. The exact mechanisms is not clear but reduction of the vascular remodeling and vascular tone in combination with reduced oxidative stress have been suggested [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“… 14 , 45 Moreover, statins could reduce endothelial dysfunction, improve vascular remodeling, and stabilize atherosclerotic plaque. 8 , 46…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 Statins, the first-line lipid-lowering therapies used widely to prevent CVD, 6 , 7 serve as a promising pharmacological strategy to improve arterial stiffness. However, recent reviews reported inconsistent findings regarding the association between statin use and arterial stiffness, with some studies 8 , 9 showing positive effects and others reporting null effects. The robustness of the evidence was limited by relatively small sample sizes (generally <100) 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 and short-term follow-up durations (generally ≤6 months).…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, statins have been prescribed for patients with higher levels of cholesterol, LDL-C, and hypertriglyceridemia in patients with cardiovascular disorders and diabetes [17,18]. However, the current line of evidence has shown that statins have numerous lipid-independent (pleiotropic) actions [19][20][21][22][23][24][25][26]. Among the pleiotropic effects of statins is modulation of autophagy in various cells, providing a promising therapeutic strategy in treating disorders with impaired autophagy as primary underlying pathogenesis [27,28].…”
Section: Introductionmentioning
confidence: 99%